Rwanda [in Strategies and priorities for African agriculture] - Diao, Xinshen; Fan, Shenggen; Kanyarukiga, Sam; Yu, Bingxin (International Food Policy Research Institute, 2012)
Despite a remarkable transition to peace and development over the past 10 years, Rwanda is still marked by the consequences of the 1994 genocide. Gross domestic product (GDP) growth averaged 7.3 percent per year between 1995 and 2006, and public investment has picked up and reached 9.4 percent of GDP in 2007. With security and political stability restored and the business environment improved, private investment has risen from 6 percent in 2001 to an estimated 9 percent of GDP in recent years (Rwanda, MINECOFIN 2008). Progress has also been made in improving education and health indicators. For examples, the number of primary school students rebounded to pre-genocide long-term levels only five years after the conflict. Today Rwanda’s gross primary school enrollment ratio is higher than in most other Sub-Saharan countries with similar income levels, and the number of students in secondary school has almost tripled since 1996 (Lopez and Wodon 2005). Moreover, in terms of health indicators, World Bank (2008a) estimates that, while infant mortality increased from 85 to 137 per thousand between 1988–92 and 1992–94, it has since receded to 97.5 per thousand in 2006.